Whole-exome sequencing identifies a novel missense variant within LOXHD1 causing rare hearing loss in a Chinese family - Na Shen; Ting Wang; Delei Li; Aiguo Liu; Yanjun Lu (BMC, 2019)
Abstract Background Deafness, autosomal recessive 77 (DFNB77) is a rare non-syndromic hearing loss (NSHL) worldwide, which is caused by deleterious variants within lipoxygenase homology domains 1 (LOXHD1). Here we identified that a novel missense variant of LOXHD1 was associated with NSHL in a Chinese family under consanguineous marriage. Case presentation A 28-year-old woman suffered a bilateral profound NSHL. Impedance audiometry, temporal bone computerized tomography (TBCT) scans and magnetic resonance imaging-inner ear hydrography (MRI-IEH) did not find any obvious abnormality of middle or inner ear. Routine genetic detection did not find pathogenic variants in common HL-associated genes. Therefore, we performed a whole-exome sequencing (WES) in this family. By trio-WES, co-segregation validation and bioinformatics analysis, we revealed that a novel homozygous variant in this patient, LOXHD1: c.5948C > T (p.S1983F), might be the pathogenic factor. Her parents (heterozygotes) and brother (wild-type) were asymptomatic. Conclusions We successfully identified a novel variant of LOXHD1 associated with a rare NSHL from a Chinese family. Our finds highlight the effectiveness of trio-WES for molecular diagnosis of rare NHSL, and expand the genotypic spectrum of DFNB77.